Intergenerational mobility: a dream deferred? - Nybom, Martin (Geneva, 2018)
"This report reviews evidence on intergenerational mobility, which measures the extent to which children’s labour market outcomes are independent of the outcomes of their parents. The report first reviews evidence on descriptive questions, documenting that mobility levels vary considerably across countries, and even across areas within countries. Mobility appears to be substantially lower in low-income than in high-income countries, but even among countries of similar income levels large differences can be seen. Moreover, in countries or areas with larger income disparities, children’s outcomes tend to depend more strongly on parental outcomes. A key focus is on the underlying drivers of intergenerational mobility: what factors and policies contribute to higher mobility? Recent research has shown that skill gaps tend to open up at a young age and then magnify through childhood. Keeping skill gaps small through childhood therefore appears crucial; for example by promoting maternal and infant health, providing widespread access to high-quality child care, and keeping the schooling system comprehensive and integrated. But the labour market is equally important, as it determines the consequences of these childhood gaps in terms of incomes and standard of living. Recent research shows that mobility differences between countries are partly due to differences in skill inequalities but that at least as much or even more is due to how labour markets reward skills and redistribute incomes. Reducing earnings inequalities and fostering employment for all may therefore also reduce intergenerational inequalities. However, causal evidence on specific labour-market factors and policies, and how they affect intergenerational mobility, is unfortunately scarce. Existing evidence points to policies that grow the middle class and provide a widespread and more equal access to good paying jobs and attractive employers. To achieve the latter, decreasing the importance of family and social networks and combatting discrimination on the labour market appear crucial."